Housing Policy, Strategy and Recent Developments in Market-based Housing Finance - Gilberto M. Llanto; Leilanie Q. Basilio (Philippine Institute for Development Studies (PIDS), 1999)
The paper discusses current government attempts to shift to market-based housing finance in the context of the past performance of the government's housing policy and strategy. It focuses on the interventions intended to provide access to the low-income groups that have been commonly excluded from formal housing credit markets. It analyzes some of the main constraints faced by low-cost housing in accessing mainstream finance, e.g., perceived affordability problems, credit risks and information asymmetry. The paper then draws attention to recent developments in market-based housing finance that can inform the government's financing strategy.
Keywords: 330; housing finance